1993
DOI: 10.1152/jn.1993.70.6.2226
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive control for backward quadrupedal walking. IV. Hindlimb kinetics during stance and swing

Abstract: 1. Hindlimb step-cycle kinetics of forward (FWD) and backward (BWD) walking in adult cats were assessed. The hindlimb was modeled as a linked system of rigid bodies and inverse-dynamics techniques were used to calculate hip, knee, and ankle joint kinetics. For swing, net torque at each joint was divided into three components: gravitational, motion dependent, and a generalized muscle torque. For stance, vertical and horizontal components of the ground-reaction force applied at a point on the paw (center of pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 0 publications
4
18
0
Order By: Relevance
“…For example, during cat backward walking, RF and sartorius anterior (hip flexors, knee extensors) are activated prior to stance and maintain activity for most of stance (Buford and Smith 1990;Pratt et al 1996), a pattern that was not observed in forward level walking or fictive locomotion in our study (Fig. 3) but is consistent with the required hip flexor and knee extensor moments during this task (Perell et al 1993).…”
Section: Activities Of Two-joint Muscles and Mechanical Demands In DIsupporting
confidence: 86%
“…For example, during cat backward walking, RF and sartorius anterior (hip flexors, knee extensors) are activated prior to stance and maintain activity for most of stance (Buford and Smith 1990;Pratt et al 1996), a pattern that was not observed in forward level walking or fictive locomotion in our study (Fig. 3) but is consistent with the required hip flexor and knee extensor moments during this task (Perell et al 1993).…”
Section: Activities Of Two-joint Muscles and Mechanical Demands In DIsupporting
confidence: 86%
“…Because the shoulder was flexing and the elbow was extending in the face of a shoulder extensor and elbow flexor contraction, it is likely that power was absorbed as these muscles undergo a lengthening (eccentric) contraction. Similar conditions exist in the hip for the iliopsoas and rectus femoris during downslope walking ] and backward walking [Perell et al, 1993]. These data suggest that the ClB and the Bi muscles retard the forward pitch of the animal due to the effects of gravity and momentum from moving down the walkway.…”
Section: Motor Pattern Changes Associated With Downslope Walkingsupporting
confidence: 57%
“…One possible explanation for these patterns in mammals is that crouched posture demands greater motor recruitment because it requires muscles to contract at lengths that are not optimal for force production (Trank et al, 1996). However, crouching might also lead to more intense bursts of motor activity in mammals because, in mammals, crouched posture increases the flexor moments of the ground reaction force about joints (Biewener, 1989(Biewener, , 1990, requiring extensor muscles to exert greater forces to keep the joints in equilibrium (Perell et al, 1993;Trank et al, 1996;Grasso et al, 2000). Because humans and cats have fairly small feet relative to the length of their hindlimb, when they use an upright limb posture they align the limb with the ground reaction force, decreasing its moment arms about the joints and, thereby, decreasing joint flexor moments and the extensor muscle forces needed to counter them in order to prevent the limb from collapsing (Biewener, 1989(Biewener, , 1990.…”
Section: Specific Muscular Mechanisms Underlying the Use Of Differentmentioning
confidence: 99%